Literature Review: Effects of Exercise on Intraocular Pressure - Alemán Ramírez, Carolina (2019)
Introduction: The relationship between intraocular pressure (IOP) and acute exercise has been studied in recent years. It has been found that acute exercise has a positive effect on IOP; however, aerobic exercise and strength exercise present different results. As for acute aerobic exercise, it can be mentioned that it provides a positive effect on the intraocular pressure since it decreases, while the strength exercise gives variability in the results obtained according to the research studies consulted. Purpose: Show the results obtained from the investigation related to the aerobic exercise and strength exercise and intraocular pressure in order to provide recommendations to healthy populations with glaucoma. Methods: The literature review searched for articles in the following databases: SportDiscus with complete text, PsycINFO, Psychology and Behavioral Sciences Collection, Rehabilitation & Sports Medicine Source, Google academics, Research Gate, PubMed.Results: Acute aerobic exercise seems to have a significant effect on intraocular pressure: it decreases it. This result occurs in sedentary people with glaucoma. For physically active people or athletes, in order to reduce IOP, it is necessary to exercise at higher intensities compared to sedentary people. Regarding the length of acute aerobic exercise, it seems that, with only 5 minutes, there is a decrease in IOP. At the end of the exercise, the acute effect of aerobic exercise seems to be maintained for a short time in the IOP; more research on  the chronic effect is necessary. Also, more research is needed and should involve variables, such as sex and age, within the study analyses and not as descriptive statistics, in order to know the effect of exercise on them. Regarding the strength exercises, the IOP increases in the upper part of the body when compared with exercises in the lower part. High-intensity strength exercises increase the IOP. Conclusions: The results show that people with normal visual condition and glaucoma can perform aerobic exercise, achieving a positive effect on their visual health. On the other hand, there is a lack of research in strength exercise; it is recommended that these studies be conducted at low intensities, according to the data obtained in this review. Regarding the quality of the studies found, the designs could be improved in the investigations. Most of these studies did not have control groups, nor did they specify the intensity; besides, they missed including descriptive aspects needed to be able to have more accurate information.